Analysis of Aquaporin-Mediated Diffusional Water Permeability by Coherent Anti-Stokes Raman Scattering Microscopy - Ibata, Keiji (The Biophysical Society, 2011)
Water can pass through biological membranes via two pathways: simple diffusion through the lipid bilayer, or water-selective facilitated diffusion through aquaporins (AQPs). Although AQPs play an important role in osmotic water permeability (P(f)), the role of AQPs in diffusional water permeability remains unclear because of the difficulty of measuring diffusional water permeability (P(d)). Here, we report an accurate and instantaneous method for measuring the P(d) of a single HeLa S3 cell using coherent anti-Stokes Raman scattering (CARS) microscopy with a quick perfusion device for H(2)O/D(2)O exchange. Ultra-high-speed line-scan CARS images were obtained every 0.488 ms. The average decay time constant of CARS intensities (τ(CARS)) for the external solution H(2)O/D(2)O exchange was 16.1 ms, whereas the intracellular H(2)O/D(2)O exchange was 100.7 ± 19.6 ms. To evaluate the roles of AQP in diffusional water permeability, AQP4 fused with enhanced green fluorescent protein (AQP4-EGFP) was transiently expressed in HeLa S3 cells. The average τ(CARS) for the intracellular H(2)O/D(2)O exchange in the AQP4-EGFP-HeLa S3 cells was 43.1 ± 15.8 ms. We also assessed the cell volume and the cell surface area to calculate P(d). The average P(d) values for the AQP4-EGFP-HeLa S3 cells and the control EGFP-HeLa S3 cells were 2.7 ± 1.0 × 10(−3) and 8.3 ± 2.6 × 10(−4) cm/s, respectively. AQP4-mediated water diffusion was independent of the temperature but was dependent on the expression level of the protein at the plasma membrane. These results suggest the possibility of using CARS imaging to investigate the hydrodynamics of single mammalian cells as well as the regulation of AQPs.